Projeto Político-Pedagógico de Escolas de Educação Básica de Ponta Grossa/PR: contradição, alienação e utopia - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
The Brazilian political situation has a severe influence on Education, since it became mandatory. As in recent periods of Brazilian history, such as during the Military Dictatorship, and in the recent globalization, connected with the global conjuncture, Education in the country has undergone several reforms and reformulations, mainly with the advent and expansion of the capitalist mode of production after the 1980s. Still, especially after the Federal Constitution of 1988, new pedagogical trends emerged for an inclusive, humanist and democratic education. With this first step coming from CF/1988, an essential document for the construction of a basic education school is the Pedagogical Political Project (PPP), guaranteed by the 1996 Law of Guidelines and Bases, which is correlated to the complexity of the school reality, containing aspects relevant to it, such as pedagogical proposals, theoretical- philosophical references, physical and structural aspects and diagnoses, in addition to being a document that provides democratic management. Since this is of fundamental importance in schools, this dissertation seeks to elucidate the participation of agents involved in the PPP of Basic Education schools in the city of Ponta Grossa, Paraná, with the purpose of: analyzing the process of democratic management, construction and potentiality of PPPs in basic education schools in the city of Ponta Grossa/PR, through an exploratory research with a qualitative approach, with the specific objectives of listing the possibilities of the PPP as a document provider of democratic management. Since this is of fundamental importance in schools, this dissertation seeks to elucidate the participation of agents involved in the PPP of basic education schools in the city of Ponta Grossa, Paraná, with the purpose of: analyzing the process of democratic management, construction and potentiality of PPPs in basic education schools in the city of Ponta Grossa/PR, through an exploratory research with a qualitative approach, with the specific objectives of listing the possibilities of the PPP as a guiding document for teaching, management democratic and student participation and reflect on the movements that permeate theory and practice with regard to the PPP. During the documentary analysis, we chose (3) PPPs from state primary and secondary schools. In data collection through interviews, (1) teacher, (1) manager and (1) student were selected to answer the questions in the interview script, which were analyzed using the Historical-Dialectic Materialism analysis method. The main authors regarding the theoretical framework of this research are Saviani (2012; 2018; 2019), Fico (1997; 2015), to list aspects of the history of Education in Brazil; Medel (2012); Veiga (2010); D. Gandin and L. A. Gandin (1997) encompassing the Political- Pedagogical Project and its particularities; Marx (2010, 2013, 2017); Marx and Engels (2007), Netto (2006; 2011), Lukács (1979; 2003; 2018), Mészáros (2006; 2008) and Cheptulin (2004). to address the categories Work, Alienation and Contradiction and to structure the data analysis from Historical and Dialectical Materialism.
Keywords: Educação; Projeto Político-Pedagógico; Emancipação; Education; Pedagogical Political Project; Emancipation; CNPQ::CIENCIAS HUMANAS::EDUCACAO